A Variety of Responses to and Engagement with J. M. Synge and W. B. Yeats in American Literary Works - Kurdi, Mária (AMERICANA E-journal of American Studies in Hungary, 2021)
This essay is concerned with the appearance of J. M. Synge and W. B. Yeats in American literature written in the last hundred years. The argument departs from recent critical ideas about the contact points between Irish and American literary production in the context of modernism. American authors who allude to, borrow and quote from various texts and themes by the two Irish writers range from Eugene O’Neill to Susan Howe. The appropriation of material rooted in Irish culture enables American writers and poets to use it in the form of intertexts and paratextual elements to enhance the scope of meanings in their own works. A scrutiny of interfaces, affinities and resonances between modern Irish and American literary texts advances knowledge about the role they can have in sustaining the powerful transnational expressiveness as a characteristic of these two literatures.